Saluran Pemasaran Peterseli (Petroselinum crispum, L) di Kecamatan Sabangau Kota Palangkaraya Kalimantan Tengah - Weni Indah Doktri Agus Tapaningsih (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2023)
Parsley was almost similary with celery that its leaves could consumed. A lot of parsley often found in Sabangau district Palangkaraya town Central Borneo. That was marketing agency role in this case. According to this matter it was needed parsley marketing role in Sabangau district Palangkaraya town Central Borneo. This research had for about august until september 2024 to be done. This research was descriptif analitic research that purposive sampling with snowball sampling to collected data. The result of this research found that there was 4 marketing agency in parsley marketing role, namely parsley peasent, wholesaler, retailer and consumer and 3 marketing role in parsley marketing, consist of marketing role I, II and III.